Djibouti : Staff-Monitored Program. (IMF Staff Country Reports; Country Report ;, 2004)
This paper on the Staff-Monitored Program (SMP) on Djibouti explains economic developments and policy discussions. Djibouti faces important challenges to reduce widespread poverty. Since the mid-1990s, the government has been engaged in adjustment and reform programs to restore macroeconomic stability and achieve sustainable economic growth. The proposed policies and reforms should be sufficient to achieve the SMP's objectives. Overall, the program will test the authorities' resolve to implement policy reforms. Steps have been taken as part of prior actions to control the wage bill and improve transparency.